Remote sensing with polarimetric radar - Mott, Harold (Wiley-Interscience, 2007)
This book presents the principles central to understanding polarized wave transmission, scattering, and reception in communication systems and polarimetric and non-polarimetric radar. Readers gain new insight into the methods for remotely gathering data about the earth's surface and atmosphere with polarimetric synthetic-aperture radar and polarimetric interferometry, including the changes that take place with seasons, floods, earthquakes, and other natural phenomena. In particular, with the book's focus on polarimetric radars, readers discover how to exploit the many special features of these systems, which provide the maximum amount of information that can be obtained remotely with radar.